Towards participatory action design research: adapting action research and design science research methods for urban informatics - Bilandzic, M.; Venable, John (Journal of Community Informatics, 2011)
This paper proposes a new research method, Participatory Action Design Research(PADR), for studies in the Urban Informatics domain. PADR supports UrbanInformatics research in developing new technological means (e.g. using mobile andubiquitous computing) to resolve contemporary issues or support everyday life in urbanenvironments. The paper discusses the nature, aims and inherent methodologicalneeds of Urban Informatics research, and proposes PADR as a method to addressthese needs. Situated in a socio-technical context, Urban Informatics requires a closedialogue between social and design-oriented fields of research as well as theirmethods. PADR combines Action Research and Design Science Research, both ofwhich are used in Information Systems, another field with a strong socio-technicalemphasis, and further adapts them to the cross-disciplinary needs and research context of Urban Informatics.